2017
DOI: 10.1037/bul0000081
|View full text |Cite
|
Sign up to set email alerts
|

Is body dissatisfaction changing across time? A cross-temporal meta-analysis.

Abstract: It remains unclear whether body dissatisfaction, a widely recognized predictor of eating-related pathologies and depressive symptomatology, is consistent across cohorts and time. This question is important to investigate because dominant theories propose that sociocultural influences, which may fluctuate, play an important role in the development of body dissatisfaction. Previous efforts for tracking body dissatisfaction across cohorts and time are limited by relying on data from a single institution or using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
143
3
13

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(170 citation statements)
references
References 403 publications
(216 reference statements)
11
143
3
13
Order By: Relevance
“…Furthermore, regrettably data about precise number of female and male students in Medicine, Literature and Philosophy were not available. We found a statistically significant difference between males and females in body uneasiness, with higher scores in the female subgroup, confirming literature data [24] for body dissatisfaction which is more common and more strongly perceived in women [39][40][41][42]. Women are more concerned about their body weight status and this may interfere with the quality of life and even become a predictor of depressed mood independently of body mass index, age and gender [39,43].…”
supporting
confidence: 87%
“…Furthermore, regrettably data about precise number of female and male students in Medicine, Literature and Philosophy were not available. We found a statistically significant difference between males and females in body uneasiness, with higher scores in the female subgroup, confirming literature data [24] for body dissatisfaction which is more common and more strongly perceived in women [39][40][41][42]. Women are more concerned about their body weight status and this may interfere with the quality of life and even become a predictor of depressed mood independently of body mass index, age and gender [39,43].…”
supporting
confidence: 87%
“…Emerging adulthood 28 or the new adolescence 29 is a developmental period for not just increased body dissatisfaction and disordered eating 30 but also for increased social media use. 31 For young and emerging adults, Snapchat, Instagram, and Facebook are the most popular SNS in the United States.…”
Section: Sns and Disordered Eating Among Young And Emerging Adultsmentioning
confidence: 99%
“…Historically, the most commonly sanctioned standard of attractiveness is the "thinideal" (i.e., a slender physique with little body fat; Thompson & Stice, 2001). However, newer research has suggested that the U.S. ideal is shifting to a more toned/athletic body as opposed to thinness (e.g., Benton & Karazsia, 2015;Karazsia, Murnen, & Tylka, 2017). College women are particularly susceptible to messages regarding expectations of weight, shape, and appearance (Fredrickson & Roberts, 1997).…”
Section: Disordered Eating Body Dissatisfaction and Social Connectionsmentioning
confidence: 99%